Development of Koha library management system: the UTM library experience/ Md Razib Karno ... [et al.] - Karno, Md Razib; Zakaria, Norhafisah; Ismail, Sharul; Md Zan, Mohamad Fahiezan; Mohd Yusof, Yusrul Hisham; Mohamed Jong, Kamariah; Othman, Haslina (Faculty of Information Management, 2021)
A library management system that can support the task of the library is cost effective, with inter module integration providing easy access to users is always a choice of any organisation. The capability of a system is integral in supporting effective and systematic learning in line with the advent of future technology. The transition from commercial system to open source KOHA is seen as factors of technology transfer, cost reduction, source code enhancement, big data analysis, innovative culture and less dependency on vendors to strengthen the implementation. This article is the recollection of UTM Library experience in developing its own open source KOHA system by librarian. Implementation of early planning, how data analysis was carried out, infrastructure development, suitable design complementing mapping and migration, implementation of real system and challenges as well as new knowledge gained along the period are documented. Transformation in librarian work culture viewpoint in the capability and direction of the library is obtained with the development of the system.